"Co-Existing Lives": Understanding and Facilitating Graduate Student Sense of Belonging. Issue 4 (2nd October 2018) - Pascale, Amanda Blakewood
Abstract : Graduate students constitute a sizable proportion of students on university campuses; still, the majority of administrative efforts focus on facilitating belonging for undergraduates exclusively. This study examines sense of belonging for graduate students and how it looks different from belongingness for undergraduate students. Research driven implications and data-based strategies for facilitating graduate student sense of belonging are discussed.